Ecophysiology of pine seedlings (Annona squamosa L.) under doses of cattle manure and irrigation depths (Research, Society and Development, 2020)
Annona squamosa is one of the most promising fruit trees in the fresh fruit market, due to its ability to adapt to edaphoclimatics, making it a good economic prospect. Thus, the objective was to evaluate the growth and physiology of Annona squamosa seedlings under doses of bovine manure and irrigation depths. The experiment was conducted in a protected environment, evaluating five irrigation depths and three doses of bovine manure, arranged in a 5 x 3 factorial scheme, in randomized blocks, with four replications and one plant per plot. The irrigation depths studied were 60, 80, 100, 120 and 140% of the actual evapotranspiration - ETr and three doses of bovine manure 0, 7.5 and 15% of the container capacity. The use of bovine manure and the management of irrigation positively influenced the gas exchange of the pine tree in its seedling phase. The supply of bovine manure at a dose of 7.5% positively influenced the growth of pine seedlings up to 54 DAT, thus being able to be used as a source of nutrients for the growth and physiology of pine.